Novel Specifications Regarding Biogas Production from Agriengineering Activities in Romania - Ioana-Ancuta Halmaciu; Ioana Ionel; Maria-Cristina Miutescu; Eugenia Grecu (AgriEngineering)
This study centers on examining the carbon/nitrogen (C/N) ratio and metal levels in various batches of manure and their potential impact on biogas production through anaerobic fermentation. A novel aspect of this research involves the utilization of nine distinct batches sourced exclusively from livestock manure found in Romanian farms, without mixing with other potential substrates. At present, the farms are not harvesting manure for energy, but they are keen to invest in biogas production in the future as a necessary step towards renewable energy in a circular economy and a bio-waste management model. As a general conclusion that is resulting, it is shown that both the C/N ratio and the content of heavy metals in animal manure must be known when dealing with the animal manure fermentation process, especially when aiming for biogas production. The C/N ratio in the analyzed samples ranges from 6.7 to 30.2. While the ideal ratio is often considered 20–30, good methane production can occur outside this range, as seen in Sample B (small pig farm), with a C/N ratio of 13.8, proving the highest methane output. This shows that the C/N ratio is important but not the only factor influencing biogas generation. The metal content in the manure samples is similar to other studies, with potassium (K) ranging from 1.64% to 8.96%. Calcium (Ca) and K are the main metals found, posing little concern. The variation in values is linked to feed recipes. Monitoring heavy metals is crucial not only for biogas production but also for the safe use of animal manure as fertilizer, as soil contamination limits must be continuously supervised. The results are also valuable for the management of waste used as fertilizer in agricultural fields in accordance with EU law.